The value added of attachment theory, research, and intervention for US child care and early childhood education: Reflecting and carrying forward the legacy of Edward Zigler. (May 2021) - Berlin, Lisa J.
Abstract: Edward Zigler pioneered and insisted upon the integration of science, practice, and policy development to support vulnerable children and families, reduce poverty, and improve US wellbeing, writ large. His far-reaching scholarship in turn critically shaped developmental science and US policy in multiple areas. This review reflects upon Zigler's influence on US child care, Head Start, Early Head Start, and prekindergarten programs. It describes the integration of one major area of developmental science, the field of attachment theory, research, and intervention, with US child care and early childhood education programs and policy. The integration of attachment into these systems not only epitomizes Zigler's overarching canon but also has improved services and advanced attachment theory and research. Throughout the review, I suggest next steps for leveraging attachment theory, research, and intervention to improve US child care and early childhood education systems in ways that both reflect and carry forward the legacy of Edward Zigler.